Effect of light on carotenoid and lipid production in the oleaginous yeast Rhodosporidium toruloides. Issue 7 (2nd July 2020) - Pham, Khanh Dung; Shida, Yosuke; Miyata, Atsushi; Takamizawa, Takeru; Suzuki, Yoshiyuki; Ara, Satoshi; Yamazaki, Harutake; Masaki, Kazuo; Mori, Kazuki; Aburatani, Sachiyo; Hirakawa, Hideki; Tashiro, Kosuke; et al.
ABSTRACT: The oleaginous yeast Rhodosporodium toruloides is receiving widespread attention as an alternative energy source for biofuels due to its unicellular nature, high growth rate and because it can be fermented on a large-scale. In this study, R. toruloides was cultured under both light and dark conditions in order to understand the light response involved in lipid and carotenoid biosynthesis. Our results from phenotype and gene expression analysis showed that R. toruloides responded to light by producing darker pigmentation with an associated increase in carotenoid production. Whilst there was no observable difference in lipid production, slight changes in the fatty acid composition were recorded. Furthermore, a two-step response was found in three genes ( GGPSI, CAR1, and CAR2 ) under light conditions and the expression of the gene encoding the photoreceptor CRY1 was similarly affected. GRAPHICAL ABSTRACT: uf0001 Light effect on carotenoid production in Rhodosporidium toruloides